Des-acylated ghrelin, rather than acylated ghrelin, might be more valuable in inflammatory bowel diseases - Aydin, Suleyman; Erman, Fazilet; Kilic, Nermin; Sahpaz, Fatih (Springer, 2008)
[Abstract Not Available]